O Instituto Brasileiro de Geografia no projeto político-cultural do Estado Novo - Oliveira, Regina Célia Acióli (2005)
The present thesis has as its object to promote the historical reconstitution of the development of statistics in Brazil, and the creation and the first years of performance of the Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística – IBGE). The period under study begins with to the creation of the Institute, in the context of the transformations provoked by the 1930 Revolution, and analyzes its participation in the moderniizing political-cultural projects in the period of the Estado Novo. The works is based, among other sources, on the documentation produced by the Institute during this time.